Information pollution as social harm : investigating the digital drift of medical misinformation in a time of crisis - Lavorgna, Anita (Emerald Publishing Limited, 2021)
The coronavirus pandemic struck the world in a very distinctive way: experience from past pandemics or from more recent outbreaks could give us only a limited understanding of how the situation was likely to unfold. In this context, and with cyberspace being increasingly used to support health- related decision making and to market health products, potentially harmful behaviours have been carried out by individuals propagating non- science- based health (mis)information and conspiratorial thinking. This includes, among other actions, boycotting the use of masks and physical distancing, proactively opposing the use of the COVID- 19 candidate vaccines, and promoting the use of useless or even dangerous substances to prevent or resist the virus. By relying on a virtual ethnography approach carried out on Italian- speaking alternative lifestyle and counter- information online communities, this book shows how the nature of personal interactions online and the construction of both personal and group identities through the development of an 'us vs. them' narrative, are central to the creation and propagation of medical misinformation. This book is essential reading for researchers in the social, health, and data sciences and also professionals interested in scientific communication.
Includes index.
Keywords: Medical misconceptions.; Fake news.; COVID-19 (Disease) -- Social aspects.; Social Science -- Criminology.; Crime & criminology.; elektronické knihy; electronic books